PENENTUAN KELAYAKAN RUANGAN PERKULIAHAN DI MASA PANDEMI MENGGUNAKAN BUILDING INFORMATION MODELLING (BIM) (STUDI KASUS: GEDUNG PRODI TEKNIK GEODESI DAN GEOMATIKA ITB) - Aflah, Hafidz
Education in Indonesia as a sub of national development requires its willingness to be able to face challenges and various problems as a consequence of the issue of globalization and pandemics. In terms of developing education so that it runs properly, every educational institution strives to provide and fulfill adequate facilities in order to meet the needs of all entities. Therefore, using Building Information Modelling (BIM) method seeks to obtain information on the facilities and feasibility of the room. The purpose of this research is was to determine the function and feasibility of the room using the BIM method Labtek IX-C Building 2nd floor, mainly Classroom 3102, TU Room, Head of Study Program, Meetings, and Toilets The methodology in this research includes data acquisition to data processing. In data acquisition, measurements were made using a Terrestrial laser scanner using the traverse & free scan method and employing ETS measurements to determine the coordinates of the control points. After that, data filtering, georeferencing, registration was carried out, followed by the 3D modelling as a determinant of the space function, and finally a database was created using 2 digital database methods and manual tables to determine the feasibility of the room. The results of the research which includes 3D models can be seen in the functions in every single of these rooms. for example, the 3102 classroom has a function for holding the teaching and learning process supported by interiors in the form of student chairs, projectors, and other objects. As for the feasibility of the room, it can be seen that Room 3102, Head of Study Program S2, Meeting Room, and Head of Study Program S1 cannot be deemed feasible because they are it is not in accordance with the health protocols. In addition, the advantage of using TLS and BIM is that they can provide precise and accurate data compared to conventional ones.